Bilateral congenital horizontal gaze palsy: MR findings - (:unkn) unknown (TAYLOR & FRANCIS AS, 1998)
Congenital horizontal gaze palsy is a rare disorder that is considered to be due to either the absence of or a lesion in the abducens nucleus. Magnetic resonance (MR) imaging of two cases with isolated congenital bilateral horizontal gaze palsy showed a lack of the normal protrusion of both abducens nuclei on the anterior wall of the fourth ventricle, These MR findings, with the support of the clinical picture of the cases, are consistent with the absence of bilateral abducens nuclei, To the best of our knowledge, this is the first report of MR evidence of the absence of abducens nuclei in horizontal gaze palsy.
Keywords: abducens nucleus; magnetic resonance; horizontal gaze palsy; Moebius syndrome; DUANES RETRACTION SYNDROME; ABDUCENS NUCLEUS; PARALYSIS; LESION